Building blocks for social accountability: a conceptual framework to guide medical schools - Preston, Robyn (BMC Med Educ, 2016)
BACKGROUND: This paper presents a conceptual framework developed from empirical evidence, to guide medical schools aspiring towards greater social accountability. METHODS: Using a multiple case study approach, seventy-five staff, students, health sector representatives and community members, associated with four medical schools, participated in semi-structured interviews. Two schools were in Australia and two were in the Philippines. These schools were selected because they were aspiring to be socially accountable. Data was collected through on-site visits, field notes and a documentary review. Abductive analysis involved both deductive and inductive iterative theming of the data both within and across cases. RESULTS: The conceptual framework for socially accountable medical education was built from analyzing the internal and external factors influencing the selected medical schools. These factors became the building blocks that might be necessary to assist movement to social accountability. The strongest factor was the demands of the local workforce situation leading to innovative educational programs established with or without government support. The values and professional experiences of leaders, staff and health sector representatives, influenced whether the organizational culture of a school was conducive to social accountability. The wider institutional environment and policies of their universities affected this culture and the resourcing of programs. Membership of a coalition of socially accountable medical schools created a community of learning and legitimized local practice. Communities may not have recognized their own importance but they were fundamental for socially accountable practices. The bedrock of social accountability, that is, the foundation for all building blocks, is shared values and aspirations congruent with social accountability. These values and aspirations are both a philosophical understanding for innovation and a practical application at the health systems and education levels. CONCLUSIONS: While many of these building blocks are similar to those conceptualized in social accountability theory, this conceptual framework is informed by what happens in practice - empirical evidence rather than prescriptions. Consequently it is valuable in that it puts some theoretical thinking around everyday practice in specific contexts; addressing a gap in the medical education literature. The building blocks framework includes guidelines for social accountable practice that can be applied at policy, school and individual levels. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12909-016-0741-y) contains supplementary material, which is available to authorized users.